Psychogeriatric experts’ experiences with risk factors of non-suicidal and suicidal self-injury in older adults: A qualitative study - Lisa Van Hove; Imke Baetens; Steven Vanderstichelen (Qualitative Research in Medicine & Healthcare)
While research has highlighted potential age-related differences in risk factors of (N)SSI, studies on such distinct risk factors in older adults are scarce. The present study addresses this gap by gaining insights into the experiences of psychogeriatric experts who work with older adults who engage in (N)SSI. In total, nine experts were interviewed regarding factors associated with (N)SSI in older adults. Responses were thematically analyzed using a biopsychosocial approach. We identified a range of biological, psychological, and social factors contributing to (N)SSI, which largely align with previous findings regardless of age. Nonetheless, cognitive and physical decline, advancing age, various experiences of loss, and social isolation emerged as particularly significant risk factors for older adults according to the experts. These results emphasize the necessity for tailored preventive measures, interventions, and screening tools to address the unique challenges faced by older adults at risk of (N)SSI. Additionally, future research should investigate (N)SSI experiences in older age through a more diverse sample, including mapping the perspective of older adults themselves, healthcare providers, and other informants, to enhance our comprehension of this phenomenon in the older population.